The Bioavailability, Potency And Distribution Of Dietary Palm Tocopherols And Tocotrienols In The Tissues Of Red Hybrid Tilapia, Oreochromis Sp. - Wang, Yan (2005)
In Experiment 1, an 8-week feeding trial was carried out to investigate the bioavailability of dietary α-tocopherol (α-T), using eight isonitrogenous and isoenergetic semi-purified diets.